PERLINDUNGAN HUKUM TERHADAP PEMBELI RUMAH YANG PERUSAHAAN PENGEMBANGNYA DINYATAKAN PAILIT (Studi Kasus: PUTUSAN PENGADILAN NIAGA JAKARTA PUSAT NOMOR: 21/PdtSus-Pailit/2020/PN.Niaga.Jkt.Pst.) - Sherly Angelina Chandra; Ariawan Gunandi (Jurnal Hukum Adigama, 2021)
Developer that is declared bankrupt can cause various legal consequences to the public, one of them is house buyer. House buyer already make Sale and Purchase Agreement with developer. However, when developer is bankrupt, then the house will be bankruptcy estate as long as the Deed of Sale and Purchase has not been proceed in the presence of a notary. In this paper, author wants to examine law protection to house buyer when the developer is bankrupt. Case is used in this paper is Central Jakarta Commercial Court Decision No: 21/Pdt-Sus-Pailit/2020/PN.Niaga.Jkt.Pst. This paper used a normative legal research method by statute approach and conceptual approach. The type of data that used in this paper is secondary data which includes primary legal materials and secondary legal materials. The result of this paper show that if viewed from Law No. 37/2004 on Bangkruptcy and PKPU, there is law protection for house buyer that bound under Sale and Purchase Agreement by registering become a concurrent creditor to get compensation. Author concluded that when a bankruptcy case occurs, the provisions used are those regulated by Law No. 37/2004 on Bankruptcy and PKPU considering that this law adheres to the principle of integration. The government should renew the bankruptcy conditions by implementing an insolvency test so that consumer creditors are protected from debtors with bad intentions, public should be careful in buying houses through the Sale and Purchase Agreement.